Characteristics and potential exposure risks of environmentally persistent free radicals in PM2.5 in the three gorges reservoir area, Southwestern China. (August 2020) - Qian, Ruozhi; Zhang, Shumin; Peng, Chao; Zhang, Liuyi; Yang, Fumo; Tian, Mi; Huang, Rujin; Wang, Qiyuan; Chen, Qingcai; Yao, Xiaojiang; Chen, Yang
Abstract: Environmentally persistent free radicals (EPFRs) are a novel class of hazardous substances that can exist stably in airborne particles for a period ranging from days to weeks and are potentially toxic to human health. Electron paramagnetic resonance spectroscopy (EPR) was used to characterize particulate EPFRs in Wanzhou in the Three Gorges Reservoir area in 2017. During the whole of 2017, the average concentration of particulate EPFRs was 7.0 × 10 13 ± 1.7 × 10 13 spins/m 3 . The seasonal concentration of EPFRs in PM2.5 showed a trend of autumn > winter > spring > summer. The maxima and minima of EPFRs occurred in spring with concentrations of 2.1 × 10 14 spins/m 3 and 9.4 × 10 12 spins/m 3 respectively. The EPFRs in PM2.5 were mainly carbon-centered radicals with adjacent oxygen atoms. Significant positive correlations were found between EPFRs and SO4 2−, NO3 − and NH4 + (r > 0.55, n = 111), indicating that EPFRs are associated with secondary sources. The atmospheric processing of particles from coal combustion, traffic, and agriculture were important sources of EPFRs. They were also particularly well correlated with K + and Cl − in winter, suggesting that EPFRs may also be derived from wintertime biomass burning emissions. The amount of inhalable EPFRs in Wanzhou was equivalent to the range of 2.3˗6.8 cigarettes per capita per day. This study provides evidence of the potential health risks of EPFRs in PM2.5, and references for air pollution control in the Three Gorges Reservoir area. Graphical abstract: Image 101427 Highlights: EPFRs in PM2.5 were mainly carbon-centered radicals with adjacent oxygen atoms. EPFRs are significantly associated with coal burnings, traffic, and secondary sources. Inhalable PM2.5 -bound EPFRs in Wanzhou was equivalent to 2.3–6.8 cigarettes per capita per day. Abstract : In Wanzhou in the Three Gorges Reservoir area, inhalable particulate EPFRs were equivalent to 2.3–6.8 cigarettes per capita per day.